JOURNALISM AND POLITICS: JOURNALISTS ON COMMUNICATION PRACTICES WITH POLITICAL ACTORS - Popovic, Helena; Rodik, Petra (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
Media and politics are related within a complex and dynamic field of interlinked institutional preactices, public policies and particular interests of diversified social groups. This paper presents one segment of the results derived from the Research on attitudes and experiences of journalists in Croatia on the openness of state bodies towards journalists, conducted for the Branch of Investigative Journalists within the Croatian Journalists’ Association. The target group were journalists that reports about the political domain, events and processes in their professional work. The presented results include modes of communication in journalists’ practices and the assessments of attributes of communication. They are interpreted within the framework of the ideology of professional journalism and the social changes that have, in the last few decades, essentially changed journalistic work. According to the survey results it is visible that journalists relate to their profession in accordance with values intrinsic to the ideology of professional journalism, however these values co-exists with ideas and practices that are in contradiction to them. Commercialization of the media and digital technologies have, to a large extent, moved journalism away from „classical” professional principles, and they have also contributed to the transformation of journalist work that is now primarily oriented towards the mastering of technological skills within a convergent environment and within which there is a deeply rooted commodified logic of action, while intellectual work has become „redundant“. Such an environment is surely not an incentive for the reflection of one’s own profession, that is, apparently, more needed than ever.